Study on the effect of mineral admixtures on working and mechanical properties of the grouting material - Shen, Quanjun; Jiang, Ruishuang; Cong, Bori; Guo, Baolin; Shang, Hongfa; Ji, Xiaoge; Li, Lianghua (Frontiers in Materials, 2023)
Aiming at the existing grouting material, there are a series of problems such as poor fluidity of the grouting , rapid loss of fluidity, non-compactness of the grouting after hardening, gaps or holes, and the like. In this paper, fly ash, limestone powder, and silica fume are used to replace cement, and the influence of mineral admixtures on the fluidity, rheological properties, and strength of the grouting material are systematically studied. The experiment found that: fly ash, limestone powder, and silica fume can all improve the fluidity of the grouting material, and the effect of fly ash is the best. Compared with pure cement grouting, the initial fluidity and 60min fluidity of the grouting material mixed with 40wt.% fly ash were reduced by 35.5% and 53.8% respectively. Fly ash and limestone powder mixed into the grouting material will significantly improve the rheological properties, while silica fume will reduce the flow properties of the grouting. The addition of fly ash and limestone powder will reduce the mechanical properties of the grouting material, while silica fume can improve the mechanical properties of the grouting material. Compared with pure cement grouting, the 28days compressive strength with 4wt.% limestone powder grouting material is reduced by 4.5%, and the flexural strength is reduced by 6%; the 28days compressive strength with 4wt.% silica fume grouting material is increased by 6.5% , the flexural strength increased by 1%.